Female Sexual Function After Radical Cystectomy: A Cross-sectional Study - Rikke Vilsbøll Milling; Anne-Dorte Seyer-Hansen; Charlotte Graugaard-Jensen; Jørgen Bjerggaard Jensen; Pernille Skjold Kingo (European Urology Open Science)
Background and objective: Radical cystectomy (RC) is the gold-standard treatment for muscle-invasive bladder cancer (MIBC). Approximately 25% of MIBC patients are women. In women, RC includes removal of the ovaries, uterus, and the anterior vaginal wall, during which nerve damage can occur, potentially impacting sexual function. Studies on sexual function among females following RC are sparse. Our aim was to investigate the impact of RC on female sexual function. Methods: A cross-sectional registry study and a questionnaire survey were used. The Danish Cancer Registry was used to identify all female patients diagnosed with MIBC between 2015 and 2020 who were treated with RC and an ileal conduit. Comorbidity and complications data were obtained from the Danish National Patient Registry. The survey included European Organization for Research and Treatment of Cancer questionnaires on quality of life (EORTC-QLQ-C30) and sexual health (EORTC-SHQ-C22) and eight questions covering female sexual function. Key findings and limitations: A total of 151 women completed the questionnaires, of whom 30 (21%) reported worries about resuming sexual activity after RC and 51 (34%) about resuming intercourse specifically. An altered perception of vaginal size was reported by 85 (56%) respondents. Prolonged time to experiencing orgasm was reported by 43 (51%) and anorgasmia by 23 (26%) of the sexually active women. Pain during and after penetration in ≥50% of attempts was reported by 29 (54%) and 23 (43%) respondents, respectively. There was moderate correlation between pain and sexual satisfaction (p < 0.001). Conclusions and clinical implications: RC can result in altered perception of vaginal size and pain on intercourse among female patients with bladder cancer, with potential effects on sexual satisfaction. Patient summary: We assessed sexual outcomes for women after removal of the bladder for bladder cancer and carried out a survey among Danish women who underwent this treatment between 2015 and 2020. The majority of the women reported changes in sexual function, including pain during intercourse and altered perception of vaginal size.